DESIGN SMART MINE EXERCISE POSITIONING USING GLOBAL POSITIONING SYSTEM (GPS) - Avando Bastari; Eko Saputra; Sunarta Sunarta; Cucuk Wahyudianto (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2020)
Marine mines are one of the supporters in securing the marine region of NKRI. In relation to marine mines, the Navy has mapped mines to the territorial waters. The importance of mine site mapping information aims to prevent landmines from being a feeding weapon for the NAVY's Alutsista. In realizing a mine-site mapping and location system that can provide geo-location information for mines using Arduino devices. Build your exercise Smart mine positioning using Global Positioning System (GPS) Neo-M6. A study in providing latitude and longitude location information is packaged using a GPS module that is connected to the Arduino processing device to obtain the location coordinates of the latitude and longitude mines. Test results of GPS-based location tracking devices are obtained by the results of location data in latitude and longitude formats. Smart Mine location identification, can be applied using GPS based on the results of the design and creation of the system that has been done. Location displacement speed calculations can be obtained by calculating the starting location with the updated location in a time span and converting to a unit of distance. Based on the results of the speed test can be obtained even if the device's location position is unchanged, this is due to the GPS data always changing due to the level of position accuracy obtained from satellites. The use of the Neo-M6 GPS can be applied to the latitude and longitude location identification systems acquired a relatively small error value with an average satellite number obtained by as much as 8 satellites. The use of the Neo-M6 GPS, to get GPS data from satellites is a long time, the problem of GPS gets satellite data due to the less supportive weather conditions. Keyword: GPS Neo-m6, Arduino Mega 2560, weather.